A Psychoanalytic Reading of ‘Marechera’S Selected Novels: Exploring the Depth of Dambudzo Marechera's Literary Works through Psychoanalytic Inquiry (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper analysesthree works of art namely ‘House of Hunger’, ‘The Black Insider’ and‘Mindblast’ by one  of  Zimbabwe’s most famous,  talented  and controversial  authors,  Dambudzo Marechera,  using mainly psychoanalytictools of inquiry. The aforementioned works of fiction have been carefullychosen to sample the writer’s skills and concerns as a poet, playwright andnovelist extraordinaire. These works, which were written between 1978 and 1984,give a fair representation of the said author’s vast and varied skills whoseworks according to one critic ‘read a little like a clever dissertation for aPhD’ (Veit-Wild, 1992: 17) yet he never completed a first degree!